Scritture umanistiche elementari (e altro) - De Robertis, Teresa (Scrineum, 2017)
What do we mean by elementary writing? What are the parameters that allow to classify a writing as elementary and to judge a scribe as unskilled? Which informations can we infer from these writings and to what extent and under what profile can they be significant for the history of writing in general (beyond the most important documents of graphic pedagogy and literacy)? On the basis of some examples mainly taken from the humanistic period, the article deals with a situation far from infrequent in the late Middle Ages (and especially in Italy in the 14th and 15th century): that of scribes capable of copying long and challenging texts, but working with a rough technique, though not lacking a rustic efficacy, based on an unstructured graphic ability (and perhaps even without intending to reach a higher skill).